2013
DOI: 10.1002/ijc.28174
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of endogenous MHC class I‐related chain molecules A and B from different human tumor entities: Heterogeneous involvement of the “a disintegrin and metalloproteases” 10 and 17

Abstract: The interaction of the MHC class I-related chain molecules A and B (MICA and MICB) with the corresponding natural killer group 2, member D (NKG2D) receptor triggers cytotoxic effector activity of natural killer cells and certain T-cell subsets and provides a costimulatory signal for cytokine production. Thus, the presence of MICA=B on transformed cells contributes to tumor immunosurveillance. Consequently, the proteolytic cleavage of MICA=B is regarded as an important immune escape mechanism of various cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(172 citation statements)
references
References 51 publications
3
152
1
3
Order By: Relevance
“…Several studies, primarily performed in different types of tumor cell lines or transfected cells in steady-state conditions, indicate the direct involvement of both ADAM10 and ADAM17 enzymes in MICA and MICB release, but the relative contribution of these enzymes is still controversial. Boutet et al (32) found that ADAM17 mediates MICB proteolytic cleavage in CV1 epithelial transfectants; however, recent evidence highlights a cell type-specific role for these metalloproteinases (33). Our results also reveal high levels of ADAM10 expression in several MM cell lines and in primary malignant PCs, with enzyme expression not correlating with the disease stage.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Several studies, primarily performed in different types of tumor cell lines or transfected cells in steady-state conditions, indicate the direct involvement of both ADAM10 and ADAM17 enzymes in MICA and MICB release, but the relative contribution of these enzymes is still controversial. Boutet et al (32) found that ADAM17 mediates MICB proteolytic cleavage in CV1 epithelial transfectants; however, recent evidence highlights a cell type-specific role for these metalloproteinases (33). Our results also reveal high levels of ADAM10 expression in several MM cell lines and in primary malignant PCs, with enzyme expression not correlating with the disease stage.…”
Section: Discussioncontrasting
confidence: 44%
“…To investigate whether drug-induced MICB release involves metalloproteinase activity (32,33), we evaluated MICB levels in the supernatants of DOX-and MEL-treated SKO-007(J3) cells in the presence of the metalloproteinase inhibitor marimastat. As MICA gene typing was performed as described in Materials and Methods.…”
Section: Inhibition Of Micb Shedding On Drug-treated Cells By Treatmementioning
confidence: 99%
See 1 more Smart Citation
“…29 Tumor shedding of the NKG2D ligands, which provide a means for tumor cell immune evasion, has been found to be regulated by ADAMs (a disintegrin and metalloproteases), 10 and 17, indicating that proteolytic cleavage of surface molecules is an undesirable characteristic of tumor cells. 30,31 The release of this NKG2D ligand is strongly associated with a systemically reduced NKG2D expression on the surface of circulating blood lymphocytes, especially cytotoxic CD56 C / CD3 ¡ NK cells, CD8 C ab and gd T cells, resulting in attenuated recognition of transformed and malignant cancer cells and decreased tumor surveillance. 10,32,33 The results of our current study confirm the impact of sMICA in the disease staging because untreated HNSCC patients diagnosed with Stage IV disease had markedly elevated sMICA levels in their blood plasma as compared with those of lower disease stages.…”
Section: E1055993-6mentioning
confidence: 99%
“…However, cancer cells promote immune escape by ectodomain shedding of MICA and produce soluble MICA that competitively inhibits NKG2D expression on the surface of NK cells. The key molecule that activates the shedding protease, including a disintegrin and metalloproteinases 9, 10 and 17, is considered to be transforming growth factor (TGF)-β (96)(97)(98). Therefore, treatments that inhibit TGF-β are important in antitumor immunity (99).…”
Section: Effect Of Preoperative Therapy On Pancreatic Cancer Tissuesmentioning
confidence: 99%